Modeling of bearing massif condition during chamber mining of ore deposits - Khomenko, O; Kononenko, M; Danylchenko, M (National Mining University, 2016)
Purpose. To examine rock mass stress changes in hanging wall and footwall rocks of the deposit during mining of primary and secondary stoping chambers. Methods. Analytical research into stress-strain state around stoping chambers was executed with the help of thermodynamical method that gives the highest convergence of calculated elastic deformations and those measured in the mine. Findings. Regularities of stress field formations in the mass of stoping chambers unloading zones are specified. The main areas of stresses concentration located in hanging wall and footwall rocks, in ore mass and backfilling are determined. The shape of radial stress isolines around stoping chambers tends towards ellipsoid. The stress level of mass around hanging wall and footwall rocks, in unloading zones of stoping chambers changes according to exponential dependences relating to the distance from ore deposit. Originality. Consists in capitalizing on the rock mass weakening effect which hosts primary and secondary stoping chambers for using rock stress value for determination of development workings site. Practical implications. The stress level of rocks around stoping chambers is defined and empirical dependencies of radial stresses values alterations in terms of changes of mining depth and proximity from ore deposit contour are specified.

Цель. Исследовать изменения напряженности массива в породах висячего и лежачего боков залежи, при отработке первичных и вторичных очистных камер. Методика. Аналитические исследования напряженно-деформированного состояния массива вокруг очистных камер выполнялись с использованием термодинамического метода, который дает наиболее высокую сходимость расчетных и измеряемых в шахте упругих деформаций. Результаты. Установлены закономерности развития полей напряжений в массиве зон разгрузки очистных камер. Определены основные области концентрации напряжений, которые располагаются в породах висячего и лежачего боков, в массиве руды и закладки. Форма изолиний радиальных напряжений вокруг очистных камер стремиться к эллипсоидной. Уровень напряженности массива пород висячего и лежачего боков, в зонах разгрузки очистных камер, изменяется по экспоненциальным зависимостям в зависимости от расстояния до рудной залежи. Научная новизна. Состоит в использовании эффекта разупрочнения массива, вмещающего первичные и вторичные очистные камеры для использования величины напряженности пород при определении места заложения полевых подготовительных выработок. Практическая значимость. Определен уровень напряженности пород вокруг очистных камер и установлены эмпирические зависимости изменения величины радиальных напряжений, учитывающие изменения глубины горных работ и удаление от контура рудной залежи.

Мета. Дослідити зміни напруженості масиву в породах висячого і лежачого боків покладу, при відпрацюванні первинних і вторинних очисних камер. Методика. Аналітичні дослідження напружено-деформованого стану масиву навколо очисних камер виконувалися з використанням термодинамічного методу, який дає найбільш високу збіжність розрахункових і вимірюваних у шахті пружних деформацій. Результати. Встановлено закономірності розвитку полів напружень у масиві зон розвантаження очисних камер. Визначено основні області концентрації напружень, які розташовуються у породах висячого і лежачого боків, у масиві руди та закладки. Форма ізоліній радіальних напружень навколо очисних камер прагне до еліпсоїдної. Рівень напруженості масиву порід висячого і лежачого боків, у зонах розвантаження очисних камер, змінюється за експоненціальними законами в залежності від відстані до рудного покладу. Наукова новизна. Полягає у використанні ефекту знеміцнення масиву, що вміщує первинні і вторинні очисні камери для використання величини напруженості порід при визначенні місця закладення польових підготовчих виробок. Практична значимість. Визначено рівень напруженості порід навколо очисних камер і встановлені емпіричні залежності зміни величини радіальних напружень, що враховують зміни глибини гірських робіт і відстань від контуру рудного покладу.
Моделювання стану вміщуючого масиву при камерному відпрацюванні запасів руд
Моделирование состояния вмещающего массива при камерной отработке запасов руд
Keywords: Research Subject Categories::NATURAL SCIENCES::Earth sciences; theoretical research; mass unloading zone; stress-strain state; chambers of primary and secondary mining stage; radial stresses